2019
DOI: 10.1177/2055217319888767
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition during a 12-week intervention with delayed-release dimethyl fumarate in multiple sclerosis – a pilot trial

Abstract: Introduction: Patients with multiple sclerosis may have a distinct gut microbiota profile. Delayedrelease dimethyl fumarate is an orally administered drug for relapsing-remitting multiple sclerosis, which has been associated with gastrointestinal side-effects in some patients. Objectives: The purpose of this study was to determine if dimethyl fumarate alters the abundance and diversity of commensal gut bacteria, and if these changes are associated with gastrointestinal sideeffects. Methods: Thirty-six patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…Moreover, there is growing evidence that sulphate-reducing bacteria, an anaerobic microorganism that belongs to normal microbiota in the gastrointestinal tract, can be a trigger of intestinal inflammation and contribute to UC [27][28][29]. Interestingly, some recent studies have shown that treatment of DMF in the patients with MS also has an impact on altering microbiota composition [30,31]. In our current study, we didn't examine the gut microbiome change.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, there is growing evidence that sulphate-reducing bacteria, an anaerobic microorganism that belongs to normal microbiota in the gastrointestinal tract, can be a trigger of intestinal inflammation and contribute to UC [27][28][29]. Interestingly, some recent studies have shown that treatment of DMF in the patients with MS also has an impact on altering microbiota composition [30,31]. In our current study, we didn't examine the gut microbiome change.…”
Section: Discussionmentioning
confidence: 90%
“…Our result that disease-modifying therapy as an individual factor had not significantly contributed to the data variance was unexpected, as previous studies revealed DMT-related differences in the gut microbiota of MS patients: the dimethyl fumarate or interferon β-b treatment decreased the Firmicutes phylum relative abundance [ 60 , 61 ]. Yet, other studies reported an increased Firmicutes abundance, mostly driven by Fecalibacterium , in the dimethyl fumarate-treated patients [ 62 ], or no difference in the Firmicutes abundance between no-DMT and DMT cohorts [ 61 ]. However, in our study the observed 2% decrease in the Fecalibacterium abundance was not statistically significant and could hardly be physiologically relevant with its negligible contribution to the data variance.…”
Section: Discussionmentioning
confidence: 99%
“…The time point of 3 months after the start of treatment was chosen in order to be able to predict early in the treatment regimen whether a treatment response can be expected. Only one previous study investigated changes in microbiota after IMT and found a trend toward changes in microbiota after 2 and 12 weeks [ 15 ]. However, possibly due to a small sample size, after correction for multiple comparisons, none of their results seem to be significant.…”
Section: Methodsmentioning
confidence: 99%